Little red riding hood activity book - Morris, Catrin (London : Ladybird books Ltd, 2016)
Little Red Riding Hood went to her grandmother's house. A wolf lived near it and he wanted to eat Little Red Riding Hood! Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Beautifully illustrated and carefully written, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills. The eight levels of Readers and Activity Books follow the CEFR framework and include language activities that provide preparation for the Cambridge English: Young Learners (YLE) exams. Little Red Riding Hood, a Level 2 Activity Book, is A1 in the CEFR framework and supports YLE Movers exams. The activities encourage children to practice short sentences containing a maximum of two clauses, introducing the past tense and some simple adverbs.
Location: 2A
Keywords: Activity book